TEACHING ENGLISH AS A FOREIGN LANGUAGE IN INDONESIA: THE URGE TO IMPROVE CLASSROOM VOCABULARY INSTRUCTION - Francisca Maria Ivone (TEFLIN Journal: A publication on the teaching and learning of English, 2005)
This article addresses some important issues regarding the teaching of foreign vocabulary. It draws on the literature reviews in this field and is also based on personal reflections and experiences of the writer. This article critically highlights the teaching of English vocabulary in Indonesian schools and universities. More particularly, it discusses issues dealing with curriculum, teaching techniques, instructional media, and vocabulary assessment. Finally, this article provides recommendations for the improvement of the teaching of English vocabulary in the Indonesian context